2015
DOI: 10.1021/cs5020332
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hydrocarbon Product Distribution and Solvent Composition in the Fischer–Tropsch Synthesis Catalyzed by Colloidal Cobalt Nanoparticles

Abstract: Colloidal cobalt nanoparticles with well-defined particle size (ca. 2.7 nm) were synthesized, characterized, and tested in Fischer−Tropsch synthesis (FTS) using water and binary mixtures as solvent. The catalytic results revealed that activity and selectivity strongly depend on the nature and composition of the solvent mixture: the tests in pure water produced light hydrocarbons (C 2 − C 4 ), while the addition of organic cosolvents increased the activity and shifted the selectivity to higher hydrocarbons (C 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…45°, 35°, and 60° ( Figure 3 ). The broadening of XRD peaks was previously observed for CoNPs prepared by chemical reduction using NaBH 4 [ 23 , 24 ], and associated to the small size and/or to the amorphous structure of the NPs [ 25 , 26 ]. Surface analysis by X-ray photoelectron spectroscopy (XPS) revealed the presence of Na, Co, O, N, C, and B. Deconvolution of the Co 2p XPS spectra (see Supporting Information) revealed that the metallic cobalt content ranged from 6% to 67% for this series of NPs.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…45°, 35°, and 60° ( Figure 3 ). The broadening of XRD peaks was previously observed for CoNPs prepared by chemical reduction using NaBH 4 [ 23 , 24 ], and associated to the small size and/or to the amorphous structure of the NPs [ 25 , 26 ]. Surface analysis by X-ray photoelectron spectroscopy (XPS) revealed the presence of Na, Co, O, N, C, and B. Deconvolution of the Co 2p XPS spectra (see Supporting Information) revealed that the metallic cobalt content ranged from 6% to 67% for this series of NPs.…”
Section: Resultsmentioning
confidence: 80%
“…This particular product distribution is attributed to mass transfer limitations when water is used as the reaction solvent due to the relatively low solubilities of CO and H 2 in water [23]. From the series of tested catalysts, Co2 and Co5 exhibited the lowest and the highest α values (0.50 vs. 0.66, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, our group reported the effect of the addition of organic co-solvents in the Aqueous phase Fischer-Tropsch Synthesis and it was concluded that the catalysis in water is strongly limited due to the extremely low syngas solubility in this solvent. [24] Regarding the product distribution, the increase of the pH from 7 to 13.3 resulted in the slight decrease of the alpha value from 0.59 to 0.52. This observation agrees with the increase of H 2 :CO ratio during the reaction under basic conditions, resulting in the increase of the chain termination rate and the production of shorter hydrocarbons.…”
Section: Accepted Manuscriptmentioning
confidence: 98%